Role of anlotinib-induced CCL2 decrease in anti-angiogenesis and response prediction for nonsmall cell lung cancer therapy. Issue 3 (7th March 2019) - Lu, Jun; Zhong, Hua; Chu, Tianqing; Zhang, Xueyan; Li, Rong; Sun, Jiayuan; Zhong, Runbo; Yang, Yuqin; Alam, Mohammad Shah; Lou, Yuqing; Xu, Jianlin; Zhang, Yanwei; et al.
Background: Anlotinib has been demonstrated in clinical trials to be effective in prolonging the progression-free survival (PFS) and overall survival (OS) of refractory advanced nonsmall cell lung cancer (NSCLC) patients. However, the underlying molecular mechanisms and predictive biomarkers of anlotinib are still unclear. Methods: A retrospective analysis of anlotinib administered to 294 NSCLC patients was performed to screen for underlying biomarkers of anlotinib-responsive patients. Transcriptome and functional assays were performed to understand the antitumour molecular mechanisms of anlotinib. Changes in serum CCL2 levels were analysed to examine the correlation of the anlotinib response between responders and nonresponders. Results: Anlotinib therapy was beneficial for prolonging OS in NSCLC patients harbouring positive driver gene mutations, especially patients harbouring the epithelial growth factor receptor (EGFR) T790M mutation. Moreover, anlotinib inhibited angiogenesis in an NCI-H1975-derived xenograft model via inhibiting CCL2. Finally, anlotinib-induced serum CCL2 level decreases were associated with the benefits of PFS and OS in refractory advanced NSCLC patients. Conclusions: Our study reports a novel anti-angiogenesis mechanism of anlotinib via inhibiting CCL2 in an NCI-H1975-derived xenograft model and suggests that changes in serum CCL2 levels may be used to monitor and predict clinical outcomes in anlotinib-administered refractory advanced NSCLC patients using third-line therapy or beyond. The underlying molecular mechanisms and predictive biomarkers of anlotinib benefitting NSCLC patients are still unclear. In this study, anlotinib-induced CCL2 decrease contributes to a novel insight for its anti-angiogenesis mechanism and responsive prediction. http://ow.ly/YZL930mXlfV